2013
DOI: 10.15560/9.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Fishes of the Salonga National Park (Congo basin, central Africa): a list of species collected in the Luilaka, Salonga, and Yenge Rivers (Equateur Province, Democratic Republic of Congo)

Abstract: A list of fishes collected in and around the periphery of the Salonga National Park in Equateur Province of the Democratic Republic of Congo is provided. While noteworthy for a wide array of rare and endangered terrestrial vertebrates, the fish fauna of the Salonga National Park, the largest protected area in Africa, is very poorly known. One hundred and fifty two species distributed in 24 families are reported on here; of which 9 represent putatively undescribed taxa currently under investigation. Lack of up-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…But dying of old age is not synonymous with being numerous. It is necessary not to extend the impression of Congo River to all the aquatic habitats of the country because studies have shown that fish diversity (e.g., Chapman, ; Hardman & Stiassny, ; Iyaba, Liyandja, & Stiassny, ; Iyaba & Stiassny, ; Munene & Stiassny, ; Plumptre et al, ), fish stocks (e.g., Aveling et al, ; Chapman, ), and fish off takes and fishing techniques (e.g., Aveling et al, ; Colom, Bakanza, Mundeka, Hamza, & Ntumbandzondo, ; Inogwabini, , Inogwabini & Lingopa, ) vary significantly depending on local conditions. The idea that the river has fish in abundance is defeated when we look at Figure below, drawn compiling published data from Harrison et al (), Vakily (), Proude (), Corsi (, ), DAFECN (), and FAO () because, as some studies (e.g., Colom et al, ; Inogwabini, ) have shown fish stocks have been declining over years in some parts of the Congo Basin in DRC, for a variety of reasons, including overexploitation (e.g., Brooks, Allen, & Darwall, ; Shumway et al, ; Thieme et al, ).…”
Section: Results and Perspectivesmentioning
confidence: 99%
“…But dying of old age is not synonymous with being numerous. It is necessary not to extend the impression of Congo River to all the aquatic habitats of the country because studies have shown that fish diversity (e.g., Chapman, ; Hardman & Stiassny, ; Iyaba, Liyandja, & Stiassny, ; Iyaba & Stiassny, ; Munene & Stiassny, ; Plumptre et al, ), fish stocks (e.g., Aveling et al, ; Chapman, ), and fish off takes and fishing techniques (e.g., Aveling et al, ; Colom, Bakanza, Mundeka, Hamza, & Ntumbandzondo, ; Inogwabini, , Inogwabini & Lingopa, ) vary significantly depending on local conditions. The idea that the river has fish in abundance is defeated when we look at Figure below, drawn compiling published data from Harrison et al (), Vakily (), Proude (), Corsi (, ), DAFECN (), and FAO () because, as some studies (e.g., Colom et al, ; Inogwabini, ) have shown fish stocks have been declining over years in some parts of the Congo Basin in DRC, for a variety of reasons, including overexploitation (e.g., Brooks, Allen, & Darwall, ; Shumway et al, ; Thieme et al, ).…”
Section: Results and Perspectivesmentioning
confidence: 99%
“…While these comparative data are minimal for the Mfimi River itself, they do provide estimated ranges for fishes from the Kasai main channel and major tributaries, and to a limited extent also for the Cuvette Centrale, and the main channel of the Congo River. Additionally, we incorporated a review of two recently published checklists, Mbimbi Mayi Munene and for the Kwilu River, a large tributary in the Kasai basin, and Monsembula Iyaba and Stiassny (2013) for rivers in the Salonga National Park in the Cuvette Centrale. While most species have not previously been reported from the Mfimi basin, for the great majority of these we believe this likely to be the result of lack of collection data rather than a true reflection of limited species' ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Information on external morphology and colouration pattern of the southern Africa species included in this study was assessed through the analysis of voucher specimens housed at the NRF‐SAIAB collection, including reference specimens whose COI sequences have been incorporated into molecular analyses (see Supplementary Material S2). Information from other Nannocharax species was obtained from original descriptions ( e.g ., Fowler, 1936; Poll, 1967; Jerep & Vari, 2013; Jerep & Vari, 2014; Jerep et al ., 2014), checklists (Vari, 2007; Munene & Stiassny, 2011; Iyaba & Stiassny, 2013; Cutler et al . 2019) and examined specimens from the Royal Museum for Central Africa (RMCA), Tervuren, Belgium, and the few congeners present in NRF‐SAIAB collection from other African ichthyofaunal regions.…”
Section: Methodsmentioning
confidence: 99%